Pathological and immunological differences of arterial thrombi and wall caused by three different periodontal bacterial injections in rat models and proposals on the pathogeneses of vascular diseases. Issue 5 (18th January 2021) - Iwai, Takehisa; Matsui, Yoshiki; Homma, Kaori; Takemura, Tamiko; Fujiwara, Mutsunori; Aoyama, Norio; Furukawa, Asuka; Sato, Hiroki; Izumi, Yuichi
Abstract: Objectives: Periodontal bacteria that have been studied show a strong connection to various vascular diseases. Among the many kinds of periodontal bacteria, Porphyromonas gingivalis ( Pg ) is well examined in the general aspects and in a rat model. However, whether other periodontal bacteria work or react differently is not studied well. Material and methods: We chose Aggregatibacter actinomycetemcomitans ( Aa ) and Prevotella intermedia ( Pi ) as different types of periodontal bacteria. Low‐density and high‐density bacterial solutions were injected in the small artery of rats' groins using our rat model. Eighteen limbs of 9 SD male rats (500–650 g) were used. After 7 days, 14–18 days, and 28 days, the rats were sacrificed. A pathological and an immuno‐histochemical study was conducted and reported on the low‐density group with 12 limbs because the Pi group lacked a high‐density study. Immuno‐histochemical staining of live Pg was performed on three limbs of three rats at 1 h, 3 h, and 1 week after injection. Results: The appearances from the acute, at 7 days, to chronic phases, at 28 days, were observed. The differences of the species were certainly observed in the internal elastic lamina (IEL), and immuno‐histochemical reactions. The inflammatory reactions, such as cellular distribution or intra‐thrombus materials, were similar in all. One week later, we could not see any living bacteria in the specimen or immunological observation. Conclusions: The three species were essentially the same, except for Aa 's stronger disruption of IEL, and more CD3 (Pan T cell) in Pi and more CD79a (Pan B cell) in Pg . We propose a new concept of a possible mechanism of vascular diseases, in which the work of LPS (lipopolysaccharides) and a toll‐like receptor (TLR) is emphasized.